The horse bone fragments from Mursa (Osijek) - Mihelić, Damir; Matolek, Zlatko A Forgač; Hincak, Zdravka (2008)
During excavation of the archaeological site Mursa (Slavonija, Croatia)large quantity of horse bone fragments were found. Material was analyzed morphometricaly with identification of sex and age at death.
Projekt MZOS
ENG